2009
DOI: 10.1074/jbc.m109.021659
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Heterogeneous Nuclear Ribonucleoprotein-recognition Region in the HIV Rev Protein

Abstract: The Rev protein is a key regulator of human immunodeficiency virus type 1 (HIV-1) gene expression. Rev is primarily known as an adaptor protein for nuclear export of HIV RNAs. However, Rev also contributes to numerous other processes by less well known mechanisms. Understanding the functional nature of Rev requires extensive knowledge of its cellular interaction partners. Here we demonstrate that Rev interacts with members of a large family of multifunctional host cell factors called hnRNPs. Rev employs amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 45 publications
5
48
0
Order By: Relevance
“…Rep proteins themselves are involved in AAV genome transcription and have been shown to affect the ratio of spliced versus unspliced AAV mRNAs (47). An increasing number of studies have suggested that various hnRNPs are involved in the replication of numerous viruses, including herpesviruses (7,23,24,33). Interestingly, some of the hnRNPs recovered were also reported to be able to associate with DNA by recognizing structural motifs and to regulate several aspects of DNA metabolism, such as chromosome maintenance and DNA replication and repair (25).…”
Section: Continued On Following Pagementioning
confidence: 99%
“…Rep proteins themselves are involved in AAV genome transcription and have been shown to affect the ratio of spliced versus unspliced AAV mRNAs (47). An increasing number of studies have suggested that various hnRNPs are involved in the replication of numerous viruses, including herpesviruses (7,23,24,33). Interestingly, some of the hnRNPs recovered were also reported to be able to associate with DNA by recognizing structural motifs and to regulate several aspects of DNA metabolism, such as chromosome maintenance and DNA replication and repair (25).…”
Section: Continued On Following Pagementioning
confidence: 99%
“…Cell Culture and Transfections-U138MG cells were cultured as described previously (46). All overexpression experiments were performed in 6-well plates.…”
mentioning
confidence: 99%
“…18,24,25 These roles in retroviral RNA splicing and nucleocytoplasmic ReseARch PAPeR trafficking might also be functionally linked 26 a notion that is supported by newer work that shows that several functionally distinct hnRNPs interact with Rev. 27 Although principally nuclear, several hnRNPs indeed have cytoplasmic functions that contribute to the localization, the utilization, and fate of RNA in the cell. [28][29][30][31] Recent work for example emphasizes the importance for hnRNPs that translocate to the cytoplasm in an HIV-1-dependent manner to contribute to vRNA stability and translation in the cytoplasm.…”
Section: Introductionmentioning
confidence: 75%
“…This could be achieved by a loss of a direct vRNA interaction and/or by the deficiency of a Rev-interacting partner. 27 While we have proposed that the hnRNP A2/B1-A2RE association is important for both nuclear Figure 6. The distribution of hnRNPs and staufen1 in polyribosome gradients.…”
Section: Discussionmentioning
confidence: 99%